Green development of Asia-Pacific cities building better cities towards 2030 - Zhao, Zheng 1979- (World Scientific, 2019)
"The book evaluates and analyses the level of green development in over 100 major cities in Asia Pacific. A quantitative analysis of the relationship with economic growth, income distribution, innovation capabilities, service sector, governance levels, and city clusters are accumulated and presented in the form of a new index; the Urban Green Development Index (UGDI). Amongst the cities discussed in the case studies are Penang (Malaysia), Singapore, Vladivostok (Russia), Portland (USA), Hamburg (Germany), and Stockholm (Sweden)"-- Provided by publisher.